An interventive and kap study on healthy lifestyle of overweight and uncontrolled diabetic patients in Kota Bharu, Kelantan - Ismail, Aziz Al-Safi; Mohamed, Mafauzy; Nordin, Rusli; Muda, Wan Abdul Manan Wan; Ibrahim, Noor (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2004)
OBJECTIVES: To assess the effects of a regular exercise programme on metabolic control and also knowledge, attitude and practice (KAP) of exercise and physical activity among Type 2 diabetes mellitus patients. MATERIAL AND MET{{ ODS: Forty two Type 2 diabetes patients from the community medicine and medical specialist clinics in USM were assigned . to two groups; The interventive group consisted of 13 males and 14 females, mean age 52.6(8.7) (mean (SD)), body mass index 27.2 (3.9) participated in regular group exercise sessions (3 times a week, 1 hour sessions) for 7 weeks. Exercise intensity was predetermined based on the predicted target heart rate for each subject. The control group consisted of 7 males and 8 females, mean age 56.5(11.1), body mass index 25.8(2.73). Pre and post-intervention anthropometric measurements and blood investigations were done. These include height, weight, body mass index, body fat percentage and fat free mass (FFM), blood pressure, cardiorespiratory fitness level, fasting plasma glucose level (FPG), HbA I c level, fasting lipid profile, insulin and Cpeptidelevel. RESULTS:, In the intervention group, FFM increased from 45.98(9.71) to 47.93(10.53) kg,; percentage body fat decreased from 32.37(11.02) to 30.14(10.73)%. Diastolic pressure reduced from 91(11.2) to 83.3(7.5) mmHg, cholesterol level decreased from 6.23(1.03) to 5.74(1.23) mmoVI, HDL level increased from 0.97(0.31) to 1.19(0.28) mmolll. Estimated V02max increased from 21.6(7.04) to 27.7(8.72) mllkg/min. Resting heart rate declined significantly from 80(7) to 73( II) bpm. There was no improvement in body mass index (BMI), fasting plasma glucose, insulin and C-peptide levels. Knowledge and attitude scores were higher than practice scores. CONCLUSION: Seven weeks of exercise intervention among type 2 diabetes patients resulted in an improvement in body composition, cardiorespiratory fitness, lipid profile and a reduction in blood pressure. However there is a disparity between knowledge and practice of exercise and physical activity.